Menimbang Gagasan Negara Hukum (Deliberatif) di Indonesia* - Fahrul Muzaqqi (Jurnal Konstitusi, 2016)
In these recent years the idea of deliberative democracy appears as an alternative idea in the middle of discourse of democracy’s contest and configuration. Through its critics which are submitted into two dominant democratic traditions (also seeking to synthesize them), viz republicanism and liberal democracy, deliberative democracy makes serious efforts to pass theoretical tensions of those two democratic traditions over by formulating a communicative participation theory in an autonomous public sphere which whom is inclusive (multi-actors), free from pressures, discrimination and manipulation.Yet, the idea of deliberative democracy self if it is observed from many deliberation literatures and practices which are studied and implemented in many countries, it has at least two variants that are mutually exclusive. First, variant of impartialism which emphasize on normative principles including the attitude and action to be inclusive, autonomous (non-partisan) and holding on the argumentation which whom considers multi-perspectives and multi-actors in taking a decision or public policy. Inter-subjectivity of an opinion was emphasized very much relating to goodness and rightness of a decision. Second, the impartialism’s critics that realizes to the real of politics and criticizes the model of impartiality that is regarded as too utopian and idealistic in applying deliberation. Principles of reciprocity, continuity, inclusivity and heterogeneity of deliberation are taken as substitute of inter-subjectivity principle in impartiality model.This paper makes a try to investigate the origin of deliberative democracy idea in modern democratic tradition. Furthermore it analyzes development of two variants of deliberative democracy idea. Finally, it endeavors to contextualize the history of Indonesian idea of democracy especially in the idea of consensus discussion (musyawarah mufakat) which is the heart of Indonesian democracy. Of course this paper uses  more historical approach to explore them   all.